The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2012
DOI: 10.1016/j.neuropsychologia.2012.09.044
|View full text |Cite
|
Sign up to set email alerts
|

Electrophysiological markers of syllable frequency during written word recognition in French

Abstract: a b s t r a c tSeveral empirical lines of investigation support the idea that syllable-sized units may be involved in visual word recognition processes. In this perspective, the present study aimed at investigating further the nature of the process that causes syllabic effects in reading. To do so, the syllable frequency effect was investigated in French using event related potentials while participants performed a lexical decision task (Experiment 1). Consistent with previous studies, manipulating the frequen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 35 publications
(64 reference statements)
1
10
0
Order By: Relevance
“…For example, Holcomb, Grainger, and O'Rourke (2002) demonstrated that words with small neighborhood size elicited larger amplitude in P200 than words with large neighborhood size did, and reading words with large neighborhood size elicited larger amplitude in N400 than reading words with small neighborhood size. Similar results have been demonstrated in studies of reading disyllabic words in Spanish, French and Basque (Barber, Vergara, & Carreiras, 2004;Chetail, Colin, & Content, 2012;VergaraMartinez, Dunabeitia, Laka, & Carreiras, 2009), and in reading Chinese characters (Hsu et al, 2009;Kong et al, 2010;Lee et al, 2007;Su, Mak, Cheung, & Law, 2012;Wu, Mo, Tsang, & Chen, 2012). In summary, these findings imply that the P200 might be associated with the early activation of orthographically/ phonologically similar words in the sublexical process.…”
Section: Introductionsupporting
confidence: 83%
See 1 more Smart Citation
“…For example, Holcomb, Grainger, and O'Rourke (2002) demonstrated that words with small neighborhood size elicited larger amplitude in P200 than words with large neighborhood size did, and reading words with large neighborhood size elicited larger amplitude in N400 than reading words with small neighborhood size. Similar results have been demonstrated in studies of reading disyllabic words in Spanish, French and Basque (Barber, Vergara, & Carreiras, 2004;Chetail, Colin, & Content, 2012;VergaraMartinez, Dunabeitia, Laka, & Carreiras, 2009), and in reading Chinese characters (Hsu et al, 2009;Kong et al, 2010;Lee et al, 2007;Su, Mak, Cheung, & Law, 2012;Wu, Mo, Tsang, & Chen, 2012). In summary, these findings imply that the P200 might be associated with the early activation of orthographically/ phonologically similar words in the sublexical process.…”
Section: Introductionsupporting
confidence: 83%
“…The times between 150 and 300 ms were chosen to span a window within which effects have been associated with processing sublexical orthography and phonology, as reported in the electrophysiology literature (e.g. Chetail et al, 2012). Next, the response latency for the ROIs was defined as the latency with the largest dSPM values, and we employed the Desikan-Killiany gyral atlas (Desikan et al, 2006) to identify the anatomical location for each ROIs.…”
Section: Regions Of Interests (Rois) and Statistical Analysismentioning
confidence: 99%
“…amplitudes observed in the current study are consistent with the interpretation that the requirement for attentional processing decreases over time with LDT learning. Alternatively, drawing from evidence of sublexical processing P200 effects [65][66][67] , our results may indicate altered reliance on sublexical processing during visual word recognition. These possibilities should be considered in future research.…”
Section: Discussionmentioning
confidence: 78%
“…Studies have found an inverse relationship between frontal P200 amplitude and the degree of supposed lexical activation that stems from early sublexical/syllable processing 62,[65][66] . For example, words with higher-frequency initial syllables are associated with weaker P200 amplitudes, compared to words with lowfrequency initial syllables, and are assumed to activate more of the lexicon during word recognition 65,67 . Conversely, greater P200 amplitudes were found when the colour boundary of a multicoloured word was mismatched from the syllable boundary, suggesting hindered syllable parsing and lexical activation 66 .…”
Section: Discussionmentioning
confidence: 99%
“…While it has been shown that sublexical characteristics like syllable-frequency as well as orthographic and phonological neighbourhood may affect the time course of print processing (e.g., Barber, Vergara, & Carreiras, 2004;Bürki, Cheneval, & Laganaro, 2015;Chetail, Colin, & Content, 2012;Hutzler et al, 2004), being restricted to a very small number of English words (see also Methods), we could not have controlled for all these potentially important linguistic factors of the stimuli. Hence, while studying early print processing we found it of utmost importance to control for lexical familiarity and visual complexity of the stimuli presented.…”
mentioning
confidence: 99%